2018
DOI: 10.1111/dme.13560
|View full text |Cite
|
Sign up to set email alerts
|

Utility of HbA1c and fasting plasma glucose for screening of Type 2 diabetes: a meta‐analysis of full ROC curves

Abstract: In our meta-analysis, we found that the optimal threshold with reference to the 2 h-PG should be chosen between 42 and 44 mmol/mol (6.0-6.2%) for HbA , and 6.2-6.4 mmol/l for fasting plasma glucose on the basis of maximal sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
3
9
3
1
Order By: Relevance
“…Our results found a lower sensitivity but slightly higher specificity for FPG (126mg/dl or 7mmol/l) detecting diabetes in undiagnosed persons than estimated by another meta-analysis [38]. Our finding of optimal cut-off of HbA1c as 6.03% for diagnosis of diagnosis in previously undiagnosed population lies within the range suggested by a previous work [18,21]; and close to optimal cut-off (6.0%) estimated by a number of included cross-sectional studies [40][41][42][43][44]. We found the certainty of evidence for the optimal threshold for sensitivity and specificity for HbA1c (6.03%) as of moderate quality (S6 Table in S1 File).…”
Section: Plos Onesupporting
confidence: 80%
See 1 more Smart Citation
“…Our results found a lower sensitivity but slightly higher specificity for FPG (126mg/dl or 7mmol/l) detecting diabetes in undiagnosed persons than estimated by another meta-analysis [38]. Our finding of optimal cut-off of HbA1c as 6.03% for diagnosis of diagnosis in previously undiagnosed population lies within the range suggested by a previous work [18,21]; and close to optimal cut-off (6.0%) estimated by a number of included cross-sectional studies [40][41][42][43][44]. We found the certainty of evidence for the optimal threshold for sensitivity and specificity for HbA1c (6.03%) as of moderate quality (S6 Table in S1 File).…”
Section: Plos Onesupporting
confidence: 80%
“…A metaanalysis by Kodama in 2013 included studies using abnormal A1c and FPG values for diagnosing and predicting diabetes [20]. Using data from previous two systematic reviews [18,20], a meta-analytical comparison of HbA1c and FPG was done by Hoyer in 2018 [21]. Another published meta-analysis reported on the summary estimates for diagnostic accuracy for HbA1c for prediabetes [19].…”
Section: Introductionmentioning
confidence: 99%
“…FPG is the fastest and simplest test used to diagnose diabetes. It also plays a role in ongoing monitoring of blood glucose control for patients with T2DM [ 29 ]. However, FPG is not the best indicator of diabetes risk.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of HbA 1c in detecting diabetes has received substantial interest [ 11 , 12 , 23 , 24 ]. In a systematic review of nine studies, Bennett, et al [ 11 ] suggested that HbA 1c at 6.1% (43 mmol/mol) could be employed as the optimal cut-off point for detecting diabetes but argued that population-specific cut-offs may vary by the population prevalence of diabetes.…”
Section: Discussionmentioning
confidence: 99%